Chemical weed control by planting of poplar (Populus) and willow (Salix) short rotation coppice - Gehring, Klaus; Festner, Thomas; Thyssen, Stefan (Julius-Kühn-Archiv, 2014)
Five field trials were carried out from 2010 – 2012 on three different locations. The trials conformed high requirement of effective weed control by planting poplar and willow short rotation coppice (SRC) on arable area. The selectivity of different pre-emergent and post-emergent herbicide treatments was tested. Further trials focused on sufficient and long-standing herbicide efficacy of tank mixture and sequence treatments. As results of these trials it is advisable to use proper soil active herbicides like Artist, Cadou SC, Sencor WG, Spectrum, Spectrum Plus or Stomp Aqua as pre-emergent tank mixture treatment after planting of poplar and willow SRC. Aramo and Lontrel 100 can be used as post-emergent treatment for control of specific weeds. We intend to register the successful tested herbicides for minor use in poplar and willow SRC under licensing referred to Art. 51 regulation (EC) no 1107/2009.